The Effect of MHC Antigen Matching Between Donors and Recipients on Skin Tolerance of Vascularized Composite Allografts. Issue 7 (8th February 2017) - Shanmugarajah, K.; Powell, H.; Leonard, D. A.; Mallard, C.; Albritton, A.; Harrington, E.; Randolph, M. A.; Farkash, E.; Sachs, D. H.; Kurtz, J. M.; Cetrulo, C. L.
Abstract : The emergence of skin‐containing vascularized composite allografts (VCAs) has provided impetus to understand factors affecting rejection and tolerance of skin. VCA tolerance can be established in miniature swine across haploidentical MHC barriers using mixed chimerism. Because the deceased donor pool for VCAs does not permit MHC antigen matching, clinical VCAs are transplanted across varying MHC disparities. We investigated whether sharing of MHC class I or II antigens between donors and recipients influences VCA skin tolerance. Miniature swine were conditioned nonmyeloablatively and received hematopoietic stem cell transplants and VCAs across MHC class I (n = 3) or class II (n = 3) barriers. In vitro immune responsiveness was assessed, and VCA skin‐resident leukocytes were characterized by flow cytometry. Stable mixed chimerism was established in all animals. MHC class II–mismatched chimeras were tolerant of VCAs. MHC class I–mismatched animals, however, rejected VCA skin, characterized by infiltration of recipient‐type CD8 + lymphocytes. Systemic donor‐specific nonresponsiveness was maintained, including after VCA rejection. This study shows that MHC antigen matching influences VCA skin rejection and suggests that local regulation of immune tolerance is critical in long‐term acceptance of all VCA components. These results help elucidate novel mechanisms underlying skin tolerance and identify clinically relevant VCA tolerance strategies. Abstract : The specificity of MHC antigen matching between donors and recipients determines skin tolerance in vascularized composite allografts in a mixed chimerism‐based miniature swine model.